Proceedings of 8th International Symposium on Heavy Flavour Physics — PoS(hf8) 1999
DOI: 10.22323/1.003.0002
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Semileptonic $B$ Decays: Dispersive Bounds and Lattice Results

Abstract: The current status of lattice and dispersive bound calculations for exclusive semileptonic B decays is reviewed. Emphasis is placed on decays relevant for the measurement of the sides of the unitarity triangle determined by |V ub | and |V cb |.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Only the lattice model predictions of UKQCD are used here. More lattice gauge predictions for the rates in these reactions, at least in some regions of q 2 , are promised soon [38] [26] with better errors. My view is that with experimental checks from measuring form-factors and unquenched lattice gauge models the errors will eventually decrease.…”
Section: Modelmentioning
confidence: 99%
“…Only the lattice model predictions of UKQCD are used here. More lattice gauge predictions for the rates in these reactions, at least in some regions of q 2 , are promised soon [38] [26] with better errors. My view is that with experimental checks from measuring form-factors and unquenched lattice gauge models the errors will eventually decrease.…”
Section: Modelmentioning
confidence: 99%
“…Only the lattice model predictions of UKQCD are used here. More lattice gauge predictions for the rates in these reactions, at least in some regions of q 2 , are promised soon [44] [27] with better errors. My view is that with experimental checks from measuring form-factors and unquenched lattice gauge models the errors will eventually decrease.…”
Section: Modelmentioning
confidence: 99%
“…Other applications of lattice QCD covered by separate talks are semileptonic decay form factors [4], quark masses [5], and quarkonia and hybrid spectrum [6]. The most recent review of lattice studies of B physics is found in [7].…”
Section: Introductionmentioning
confidence: 99%